Iron oxyhydroxide supported activated carbon adsorbent and method for preparing the same

CN122999142APending Publication Date: 2026-10-30HUNAN CARBON BAMBOO NEW MATERIAL TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611385223.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]共沉淀混合法虽可将氧化铁直接与活性炭复合,但铁氧化物主要分布于颗粒外表面或大孔区域,难以进入微孔和介孔内部

Benefits of technology

[0024]优选的,所述的铁羟基氧化物负载活性炭吸附剂作为固定床滤料用于水中除砷和/或除磷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999142A_ABST
    Figure CN122999142A_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing an iron hydroxyl oxide-supported activated carbon adsorbent, comprising the following steps: S1, using activated carbon particles as raw material, the activated carbon particles adsorb a precursor liquid to obtain wetted particles containing the precursor liquid within the carbon pores; S2, removing the continuous free liquid from the outer surface of the activated carbon particles; S3, subjecting the activated carbon particles to a gel permeation and desolvation treatment; after the permeation and desolvation treatment, separating the activated carbon particles from the gel; S4, subjecting the activated carbon particles to an alkalization treatment using a gas-phase alkalization method; S5, subjecting the activated carbon particles to aging, washing, and drying treatments sequentially to obtain the iron hydroxyl oxide-supported activated carbon adsorbent. This invention can achieve uniform loading and precise control of iron-based active components, avoid excessive deposition on the outer surface, and when applied to water treatment, the adsorbent can improve the adsorption capacity of arsenic and phosphorus while increasing treatment efficiency and reducing the leaching rate of iron from water washing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of adsorbent preparation technology, specifically to iron hydroxyl oxide supported activated carbon adsorbent and its preparation method. Background Technology

[0002] In existing technologies, activated carbon composite materials supported on iron oxides or iron hydroxyl oxides combine the physical adsorption capacity of activated carbon with the chemical affinity of iron-based materials for specific anions. These composites can be used to remove low-concentration, highly toxic pollutants from water, such as deep removal of phosphates, removal of highly toxic metals like arsenic or antimony, and removal of organic matter like dyes. Preparation methods for these activated carbon composite materials typically include iron salt impregnation and drying, co-precipitation mixing, and high-temperature calcination. For example, Chinese patent CN102614854A discloses a method for preparing an iron-loaded activated carbon adsorbent for phosphorus removal, which involves acid-treating activated carbon, mixing it with an inorganic iron salt solution, stirring, and drying to obtain iron-loaded activated carbon. Patent CN100386141C discloses an arsenic removal composite adsorbent and its preparation method, which first prepares an iron oxide suspension, then mixes activated carbon with the iron oxide suspension to obtain a composite material. Patents such as CN102114401B also report similar methods for preparing iron-loaded activated carbon.

[0003] While co-precipitation mixing can directly combine iron oxide with activated carbon, the iron oxide is mainly distributed on the outer surface of the particles or in the macroporous region, making it difficult to penetrate into the micropores and mesopores. High-temperature calcination has problems such as high energy consumption, easy agglomeration of iron oxide, and destruction of pore structure. In the ordinary impregnation-drying method, moisture mainly evaporates from the outer surface of the particles, and the liquid inside the pores continuously generates capillary replenishment to the outer surface. Iron precursors migrate to the outer layer of the particles and the pore openings with the liquid, resulting in crusting on the outer surface, large particle deposition at the pore openings, and insufficient utilization of the internal pores. If liquid alkali is added directly to the wet particles for hydrolysis, precipitation may preferentially form outside the pores, and the unfixed iron precursors may be carried out by the liquid phase. If only polymer solutions are used for dehydration, problems such as polymers entering the macropores, precursors diffusing outwards at the same time, and a large amount of free liquid remaining on the outer surface of the particles may occur.

[0004] Therefore, how to achieve uniform loading and precise control of iron-based active components within the pores of activated carbon while avoiding excessive deposition on the outer surface remains a pressing technical problem in this field. This invention aims to develop an iron hydroxyl oxide-supported activated carbon adsorbent and its preparation method to better meet practical needs. Summary of the Invention

[0005] The technical problem solved by this invention is to provide an iron hydroxyl oxide-supported activated carbon adsorbent and its preparation method, which achieves uniform loading and precise control of iron-based active components inside the activated carbon channels, avoids excessive deposition on the outer surface, and thus improves the adsorption capacity of arsenic and phosphorus.

[0006] The technical problem solved by this invention is achieved by the following technical solution: The preparation method of iron hydroxyl oxide supported activated carbon adsorbent includes the following steps: S1. Using activated carbon particles as raw material, the activated carbon particles adsorb a precursor liquid to obtain wetted particles containing the precursor liquid in the carbon pores; the precursor liquid includes an iron carboxylic acid complex. Preferably, the activated carbon particles comprise one or more of biomass-based activated carbon, coal-based activated carbon, and resin-based activated carbon. Preferably, the activated carbon particles have a particle size of 0.3~3.0 mm and a BET specific surface area of ​​500~2200 m². 2 / g, total pore volume is 0.2~1.5 cm³ 3 / g. Preferably, the activated carbon granules are pretreated by washing, drying and sieving.

[0007] S2. Remove the continuous free liquid from the outer surface of the activated carbon particles treated in step S1, so that the surface of the wet particles remains wet but there is no continuous liquid phase that can flow between the particles. S3. The activated carbon particles treated in step S2 are subjected to a gel permeation and desolvation treatment; after the permeation and desolvation treatment is completed, the activated carbon particles are separated from the gel; the gel is covalently connected to anionic groups that maintain a negative charge under the treatment conditions and do not migrate with the aqueous phase. S4. The activated carbon particles treated in step S3 are alkalized by gas-phase alkalization. S5. The activated carbon particles treated in step S4 are subjected to aging, washing and drying processes in sequence to obtain the iron hydroxyl oxide supported activated carbon adsorbent.

[0008] Furthermore, in step S1, the pH value of the precursor solution is 4.5 to 5.5, and the molar concentration of iron in the precursor solution is 0.8 to 2.0 mol / L.

[0009] Preferably, the ferric carboxylic acid complex includes one or more of ferric ammonium citrate, ferric citrate, ferric gluconate, and ferric lactate.

[0010] Further preferably, 0.05–0.15 mol / L of citrate is added to the precursor solution to improve the complexation stability of Fe(III) during the precursor solution and pore wetting process, and to inhibit premature hydrolysis, aggregation or precipitation before entering the activated carbon pores and permeating and desolvating.

[0011] Further, in step S1, the activated carbon particles and the precursor solution are placed in a vacuum container and adsorbed at a pressure of -0.04 to -0.095 MPa for 2 to 30 minutes, after which the pressure is released, and then allowed to stand for adsorption for 15 to 120 minutes. In this step, during the process of maintaining negative pressure in the vacuum container and subsequently restoring it to normal pressure, the precursor solution enters the carbon channels inside the activated carbon particles and completes pre-adsorption on the pore walls, thereby obtaining moistened particles containing the precursor solution within the pore channels of the activated carbon particles.

[0012] Furthermore, in step S2, one or more of the following methods are used to remove the continuous free liquid on the surface of the activated carbon particles: centrifugal dehydration, air knife purging, rolling leaching, or short-time adsorption. After treatment, the mass of the free liquid carried over to the wetted particles is 8-15% of the dry weight of the activated carbon. In this step, the surface of the activated carbon particles remains moist, but there is no flowing continuous liquid phase between the particles. This operation aims to retain only the pore liquid inside the pores and near the pore walls of the activated carbon particles, so that subsequent gel absorption mainly acts on the liquid phase inside the activated carbon pores. If a large amount of continuous free liquid still exists outside the particles, the gel will preferentially absorb the external liquid, and the iron precursor will easily migrate with the liquid to the outer surface of the particles or the gel side, thereby weakening the selective concentration effect within the pores.

[0013] Furthermore, in step S3, the gel is an exclusion-type cross-linked polymer gel, and the anionic groups contained in the gel are carboxyl groups, carboxylate groups, sulfonate groups, or sulfate groups.

[0014] More preferably, the gel comprises one or more of cross-linked sodium polyacrylate gel and cross-linked sodium carboxymethyl cellulose gel. The cross-linked sodium polyacrylate gel and cross-linked sodium carboxymethyl cellulose gel are commercially available pre-cross-linked absorbent gels, which undergo pre-absorption and swelling treatment with deionized water before use. The equilibrium water absorption ratio of the gel in deionized water at 25 °C is 150–350 g / g.

[0015] Preferably, the pre-absorbed water content of the gel is 25-60% of its equilibrium water absorption capacity. This is used to adjust the remaining water absorption capacity and osmotic driving force, avoiding excessively dry gel causing localized rapid dehydration or excessively wet gel leading to insufficient water absorption capacity.

[0016] In this step, the network framework of the gel cannot freely enter the target pores of the activated carbon. The anionic groups fixed by the gel generate electrostatic repulsion against the ferric carboxylic acid precursor existing in anionic complex form. Under the action of gel water absorption and osmotic pressure, some water in the activated carbon pores migrates to the gel side, while the ferric carboxylic acid precursor in the activated carbon pores is preferentially retained and concentrated in the pores due to pore wall pre-adsorption, size hindrance and like charge repulsion.

[0017] Furthermore, in step S3, the mass ratio of the moistened particles to the gel is 1:1~3; the gel is pre-treated with water before contacting the activated carbon particles; the contact temperature between the moistened particles and the gel is 10~40 ℃, and the contact time is 30~120 min; the permeation and desolvation treatment is carried out in a closed container, and the total mass loss of the moistened particles and the gel during the permeation and desolvation process does not exceed 2%, so as to suppress the influence of air evaporation on the migration of precursors in the activated carbon particles.

[0018] Furthermore, in step S4, the gas-phase alkalization method involves alkalizing the activated carbon particles with ammonia vapor and / or ammonia-containing humid gas generated by heating ammonium bicarbonate. The treatment temperature is 20–70 °C, and the treatment time is 1–12 h. In this step, the activated carbon particles do not come into contact with the liquid. The ferric carboxylic acid complex precursor within the activated carbon particles undergoes in-situ hydrolysis to form amorphous or low-crystallinity iron hydroxyl oxides.

[0019] Further, in step S5, the activated carbon particles treated in step S4 are aged at 40–90 °C and 70–95% relative humidity for 2–12 h, washed with deionized water, and then dried at 70–120 °C for 6–12 h. In this step, the deionized water washing is mainly used to remove free salts and unfixed ferric carboxylic acid complexes from the surface of the activated carbon particles. The gel separated in step S3, after being washed with water and its moisture content readjusted, can be reused for the next batch of permeation and solvent extraction treatment.

[0020] An iron hydroxyl oxide-supported activated carbon adsorbent is prepared by the method described above, wherein the BET specific surface area ratio of the iron hydroxyl oxide-supported activated carbon adsorbent to the activated carbon granule raw material is 45~90:100.

[0021] The adsorbent particles prepared by this invention have more iron distributed inside the particles rather than forming a crust on the outer surface. At the same time, the iron hydroxyl oxides are kept in a nano-dispersed state. The average particle size of the iron hydroxyl oxides in the adsorbent particles is preferably 1~10 nm, which helps to reduce pore blockage and iron particle agglomeration, improve the utilization rate of effective iron sites, and reduce iron leaching caused by water flow.

[0022] The application of the iron hydroxyl oxide-supported activated carbon adsorbent in water treatment.

[0023] Furthermore, the iron hydroxyl oxide-supported activated carbon adsorbent is used for the adsorption and removal of As(V), As(III), phosphates, antimonates, or other oxygen-containing anions in water that have an affinity for iron hydroxyl oxides.

[0024] Preferably, the iron hydroxyl oxide-supported activated carbon adsorbent is used as a fixed-bed filter media for the removal of arsenic and / or phosphorus from water.

[0025] Beneficial effects: The iron hydroxyl oxide-supported activated carbon adsorbent and its preparation method described in this invention involve the precursor liquid with pore wall affinity being pre-introduced into the internal pores of activated carbon particles. After the continuous liquid phase on the outer surface of the activated carbon particles is removed, they are contacted with a gel containing fixed anionic groups under sealed conditions. The gel absorbs water, causing some of the solvent inside the pores to migrate to the gel side, and more of the iron carboxylic acid complex precursor is retained in the pores, thereby achieving high loading through in-situ conversion in subsequent processes. Subsequently, slow gas-phase alkalization is used to concentrate the precursor and convert it in-situ near the pore wall, thereby reducing outer layer migration and liquid phase loss.

[0026] This invention pre-loads a functional precursor solution into pre-formed rigid activated carbon channels, then uses an external cross-linking gel to extract the solvent from the pores. This differs from conventional techniques such as emulsion droplet solidification, hydrogel dehydration, or polymer film formation in both object and effect. This invention removes continuous free liquid from the particle surface before permeation and solvent extraction, and suppresses air evaporation under sealed conditions, reducing the migration of evaporation-driven iron precursors to the outer surface and minimizing outer crust formation. Furthermore, the gel used in this invention simultaneously provides cross-linking network size exclusion, like-charge repulsion of fixed anionic groups, and water absorption osmotic pressure. The gel is well-matched with the anionic ferric carboxylic acid complex precursor, facilitating water migration while retaining the iron precursor within the pores. The slow gas-phase alkalization, replacing the traditional method of direct immersion in large amounts of liquid alkali, reduces the risk of unfixed iron precursors being carried out by the external liquid phase and the risk of instantaneous precipitation outside the pores. Under the same iron loading, the iron hydroxyl oxides dispersed within the activated carbon pores help reduce large particle aggregation and direct water scouring, while also considering the adsorption sites for oxygen-containing anions and the remaining pore structure of the activated carbon.

[0027] The iron hydroxyl oxide-supported activated carbon prepared by this invention can achieve uniform loading and precise control of iron-based active components inside the activated carbon channels, and avoid excessive deposition on the outer surface. Compared with ordinary impregnated and dried samples and ordinary commercial activated carbon, the material of this application exhibits smaller iron phase particle size, higher pore structure retention rate, lower iron leaching rate and better cycle stability. Attached Figure Description

[0028] Figure 1The microstructure and phase characterization of the iron hydroxyl oxide-supported activated carbon obtained in Example 1 are shown below. a) is the SEM image of the sample from Example 1 and the surface distribution of Fe, O, C, and Si elements; b) is the TEM image of the sample from Example 1 and the particle size distribution of iron hydroxyl oxide nanoparticles; c) is the HAADF-STEM image and a magnified view of a portion of the sample from Example 1; d) shows the elemental distribution of Fe, O, and C in the indicated region; e) from top to bottom are the XRD patterns of the original activated carbon raw material, the ordinary impregnated sample from Control Example 1, and the iron hydroxyl oxide-supported activated carbon in the pores of Example 1; f) from top to bottom are the Raman spectra of the original activated carbon raw material, the ordinary impregnated sample from Control Example 1, and the iron hydroxyl oxide-supported activated carbon in the pores of Example 1.

[0029] Figure 2 The image shows a SEM image (1 μm) of the sample from Example 1.

[0030] Figure 3 The image shows a SEM image (10 μm) of the sample from Example 1.

[0031] Figure 4 The image shows the SEM image (1 μm) of the control sample 1.

[0032] Figure 5 The image shows the SEM image (10 μm) of the sample in Control Example 3. Detailed Implementation

[0033] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below with reference to specific embodiments.

[0034] Example 1

[0035] The preparation method of the iron hydroxyl oxide supported activated carbon adsorbent described in this embodiment includes the following steps: S1. Bamboo-based activated carbon granules are used as raw materials. The bamboo-based granular activated carbon has a particle size of 1.5–2.5 mm after sieving and a BET specific surface area of ​​950–1350 m². 2 / g, total pore volume is 0.80~1.25 cm³ 3 / g. Bamboo-based activated carbon granules were washed with deionized water, dried at 105 °C for 8 h, cooled, and sealed for later use.

[0036] Take 10g of dried bamboo-based activated carbon granules and prepare 100 mL of precursor solution. The precursor solution is ferric ammonium citrate solution with a molar concentration of 1.5 mol / L for iron. In addition, add an appropriate amount of sodium citrate with a concentration of 0.1 mol / L to improve the complexation stability of Fe(III). Use citric acid to adjust the pH of the precursor solution to 5.0. Activated carbon particles and precursor solution were placed in a vacuum container and kept under a gauge pressure of -0.080 MPa for 5 min. After venting, the pressure was restored to normal within 5 min, and then allowed to stand for 30 min. This allowed the ferric carboxylic acid in the precursor solution to enter the pores and pre-adsorb onto the oxygen-containing sites on the pore walls, resulting in wetted particles containing precursor solution in the carbon pores. S2. After filtering the activated carbon particles treated in step S1, centrifuge them at a rate of 1000 r / min for 2 min to remove the continuous free liquid on the outer surface of the particles and between the particles, so that the surface of the wet particles remains wet but there is no flowable continuous liquid phase between the particles. The mass of the free liquid carried by the wet particles after centrifugation is about 12% of the dry weight of the activated carbon. S3. The activated carbon particles treated in step S2 are subjected to a gel permeation and desolvation treatment. A commercially available pre-crosslinked sodium polyacrylate hydrogel is used, with an equilibrium water absorption ratio of approximately 250 g / g in deionized water at 25 ℃. Before use, the activated carbon particles are pre-absorbed to 35% of their equilibrium water absorption capacity. The activated carbon particles are placed in an inert mesh bag with a pore size of 100 μm, ensuring that both sides of the mesh bag are in contact with the gel. The mass ratio of activated carbon particles to pre-absorbed gel is 1:2. The particles are then contacted in a sealed container at 25 ℃ for 60 min. The total mass loss of the moistened activated carbon particles and gel before and after treatment is controlled to be less than 1%. After the permeation and desolvation treatment is completed, the activated carbon particles are separated from the gel. S4. Immediately place the activated carbon particles treated in step S3 into a gas-phase alkalization container for alkalization treatment. Specifically, place 2% ammonia water at the bottom of the container, ensuring that the activated carbon particles do not come into direct contact with the ammonia water; treat at 35 °C for 2 hours.

[0037] S5. The activated carbon particles treated in step S4 are subjected to aging, washing and drying treatments in sequence. The aging treatment is carried out at 60 °C and a relative humidity of about 90% for 4 h. The washing is carried out with deionized water until the conductivity of the washing solution is less than 100 μS / cm. The drying is carried out under vacuum at 80 °C for 8 h. After drying, the iron hydroxyl oxide supported activated carbon adsorbent is obtained.

[0038] Example 2

[0039] In this embodiment, in step S1, the molar concentration of iron in the ferric ammonium citrate solution in the precursor solution is 0.8 mol / L, the concentration of sodium citrate is maintained at 0.10 mol / L, and the rest is the same as in Example 1.

[0040] Example 3

[0041] In this embodiment, in step S1, the molar concentration of iron in the ferric ammonium citrate solution in the precursor solution is 2.0 mol / L, the concentration of sodium citrate is maintained at 0.1 mol / L, and the rest is the same as in Example 1.

[0042] Example 4

[0043] In this embodiment, the pre-absorption degree of the cross-linked sodium polyacrylate gel in step S3 is 25% of the equilibrium water absorption, the mass ratio of the moistened activated carbon particles to the pre-absorbed gel is maintained at 1:2, and the rest is the same as in Example 1.

[0044] Example 5

[0045] In this embodiment, the pre-absorption degree of the cross-linked sodium polyacrylate gel in step S3 is 50% of the equilibrium water absorption, the mass ratio of the moistened activated carbon particles to the pre-absorbed gel is maintained at 1:2, and the rest is the same as in Example 1.

[0046] Example 6

[0047] In this embodiment, the permeation and desolvation time in step S3 is 45 min, and the rest is the same as in Example 1.

[0048] Example 7

[0049] In this embodiment, the permeation and desolvation time in step S3 is 90 min, and the rest is the same as in Example 1.

[0050] Example 8

[0051] In this embodiment, in step S3, the gel is a cross-linked sodium carboxymethyl cellulose gel. A commercially available pre-cross-linked sodium carboxymethyl cellulose hydrogel is used, which has an equilibrium water absorption ratio of approximately 280 g / g in deionized water at 25 °C. Before use, it is pre-absorbed to 35% of its equilibrium water absorption capacity. The rest is the same as in Example 1.

[0052] Example 9

[0053] The material was prepared by scaling up the process of Example 1. The resulting material was packed into a glass adsorption column with an inner diameter of 20 mm and a bed height of 150 mm. Dynamic filtration was performed using simulated water containing As(V) or phosphate, and the empty bed contact time was controlled to be 5-20 min. The breakthrough curve, iron leaching, and reusability after regeneration were recorded.

[0054] Compare with Example 1 In this comparative example, the preparation method of the iron hydroxyl oxide-supported activated carbon adsorbent includes the following steps: S1. Using bamboo-based activated carbon granules as the raw material, the same as in Example 1, the granules were washed with deionized water, dried at 105 °C for 8 h, cooled and stored for later use. Take 10g of dried bamboo-based activated carbon granules and prepare 100 mL of precursor solution. The precursor solution is ferric ammonium citrate solution with a molar concentration of 1.5 mol / L for iron. In addition, add sodium citrate with a concentration of 0.1 mol / L to improve the complexation stability of Fe(III). Use citric acid to adjust the pH of the precursor solution to 5.0. Activated carbon particles and precursor solution were placed in a vacuum container and kept under a gauge pressure of -0.080 MPa for 5 min. After venting, the pressure was restored to normal within 5 min, and then allowed to stand for 30 min. This allowed the ferric carboxylic acid in the precursor solution to enter the pores and pre-adsorb onto the oxygen-containing sites on the pore walls, resulting in wetted particles containing precursor solution in the carbon pores. S2. After filtering the activated carbon particles treated in step S1, dry them in an 80°C forced-air oven. S3. Immediately place the activated carbon particles treated in step S2 into a gas-phase alkalization container for alkalization treatment. Specifically, place 2% ammonia water at the bottom of the container, ensuring that the activated carbon particles do not come into direct contact with the ammonia water; treat at 35 °C for 2 hours.

[0055] S4. The activated carbon particles treated in step S3 are subjected to aging, washing and drying treatments in sequence. The aging treatment is carried out at 60 °C and a relative humidity of about 90% for 4 h. The washing is carried out with deionized water until the conductivity of the washing solution is less than 100 μS / cm. The drying is carried out under vacuum at 80 °C for 8 h. After drying, the iron hydroxyl oxide supported activated carbon adsorbent is obtained.

[0056] Compare with Example 2 In this comparative example, the preparation method of the iron hydroxyl oxide-supported activated carbon adsorbent includes the following steps: S1. Using bamboo-based activated carbon granules as the raw material, the same as in Example 1, the granules were washed with deionized water, dried at 105 °C for 8 h, cooled and sealed for later use. Take 10g of dried bamboo-based activated carbon granules and prepare 100 mL of precursor solution. The precursor solution is ferric ammonium citrate solution with a molar concentration of 1.5 mol / L for iron. In addition, add sodium citrate with a concentration of 0.1 mol / L to improve the complexation stability of Fe(III). Use citric acid to adjust the pH of the precursor solution to 5.0. Activated carbon particles and precursor solution were placed in a vacuum container and kept under a gauge pressure of -0.080 MPa for 5 min. After venting, the pressure was restored to normal within 5 min, and then allowed to stand for 30 min. This allowed the ferric carboxylic acid in the precursor solution to enter the pores and pre-adsorb onto the oxygen-containing sites on the pore walls, resulting in wetted particles containing precursor solution in the carbon pores. S2. After filtering the activated carbon particles treated in step S1, centrifuge them at a rate of 1000 r / min for 2 min to remove the continuous free liquid on the outer surface of the particles and between the particles, so that the surface of the wet particles remains wet but there is no flowable continuous liquid phase between the particles. The mass of the free liquid carried by the wet particles after centrifugation is about 12% of the dry weight of the activated carbon. S3. The activated carbon particles treated in step S2 are left to stand in a sealed container at 25 °C for 60 min, and then immediately placed in a gas phase alkalization container for alkalization treatment. Specifically, 2% ammonia water is placed at the bottom of the container, and the activated carbon particles are not in direct contact with the ammonia water. The treatment is carried out at 35 °C for 2 h.

[0057] S4. The activated carbon particles treated in step S3 are subjected to aging, washing and drying treatments in sequence. The aging treatment is carried out at 60 °C and a relative humidity of about 90% for 4 h. The washing is carried out with deionized water until the conductivity of the washing solution is less than 100 μS / cm. The drying is carried out under vacuum at 80 °C for 8 h. After drying, the iron hydroxyl oxide supported activated carbon adsorbent is obtained.

[0058] Compare with Example 3 Compared with Example 1, this comparative example omits the centrifugation to remove continuous free liquid in step S2 and directly proceeds to the permeation desolvation treatment in step S3. The rest is the same as in Example 1.

[0059] Compare with Example 4 Compared with Example 1, in step S3, a 25% (w / w) polyethylene glycol aqueous solution was used to replace the gel, and the mass ratio of the wetted particles to the polyethylene glycol aqueous solution was 1:2, so that the wetted particles were in direct contact with the polyethylene glycol aqueous solution for 60 minutes. The rest was the same as in Example 1.

[0060] Compare with Example 5 Compared with Example 1, in step S3, the gel in this comparative example is replaced by a cross-linked polyethylene glycol neutral gel without fixed ionic groups. The cross-linked polyethylene glycol neutral gel is a commercially available product. Before use, it is pre-absorbed with deionized water to 35% of its equilibrium water absorption capacity. The rest is the same as in Example 1.

[0061] Compare with Example 6 This comparative example uses commercially available NORIT® GAC 1240W activated carbon as the commercial reference sample. Before use, it was quickly washed with deionized water and dried at 105 °C for 8 h without iron precursor loading, gel permeation desolvation, or subsequent alkalization treatment.

[0062] The materials obtained from each embodiment and comparative example were tested. The test methods are as follows: 1) The total iron content and iron loss in the external gel were determined using ICP-OES; after embedding and slicing the material particles, SEM-EDS or micro-area X-ray fluorescence was used for line scanning along the particle radius to evaluate the spatial distribution of Fe from the outer layer to the inner region of the particles; TEM was used to analyze the particle size and dispersion state of iron hydroxyl oxides, and XRD was used to analyze their phase composition and crystallization characteristics. The results are as follows: Figure 1 As shown; 2) The BET specific surface area, total pore volume, and micropore volume of the material were tested using nitrogen adsorption-desorption; the results are shown in Table 1.

[0063] 3) Prepare single-component solutions with initial As(V) and phosphate concentrations of 20-200 mg / L respectively. Then, weigh 0.100 g of material and add it to 100 mL of the solution. Adjust the pH to 6.0 and shake at 25 ℃ and 150 r / min for 24 h. Determine the equilibrium concentration and calculate the adsorption capacity. Kinetic tests were performed by sampling within 5-1440 min. Iron leaching tests were conducted using deionized water, pH 4.0 buffer water, and brine containing coexisting sulfate / bicarbonate. The adsorbent was regenerated using 0.05-0.20 mol / L alkaline salt solutions, and five adsorption-desorption cycles were performed. The results are shown in Table 2.

[0064] 4) As shown in Table 3, the ordinary impregnation-drying samples of Example 9, Control Example 1, and Control Example 6 NORIT® GAC1240 W commercially available granular activated carbon were recorded with the same packing mass, bed height, and influent concentration, and the breakthrough curves, dynamic adsorption capacity per unit mass, bed pressure drop, and effluent iron concentration were recorded and compared. The results are shown in Table 4.

[0065] Table 1. Record of iron distribution and pore structure results for materials in each embodiment and control example.

[0066] Table 2. Record of adsorption, leaching, and recycling results for materials in each embodiment and control example.

[0067] Table 3 Fixed Bed Test Conditions

[0068] Table 4. Statistical comparison of fixed bed performance in Example 9, Comparative Example 1, and Comparative Example 6

[0069] Depend on Figure 1It can be seen that the iron hydroxyl oxide-supported activated carbon prepared by this invention maintains the original particle and porous framework morphology of activated carbon. Fe and O elements are relatively uniformly distributed in the carbon framework region, and no obvious large-size continuous iron phase covering layer is observed. TEM results show that the iron hydroxyl oxide is dispersed in the carbon matrix in the form of nanoparticles with an average particle size of about 2.3 nm. HAADF-STEM and corresponding elemental surface distribution further show that the bright contrast nano-regions have a good spatial correspondence with the distribution of Fe and O elements, indicating that the iron-based components can achieve relatively dispersed loading in the activated carbon framework. XRD results show that the sample of Example 1 shows characteristic diffraction peaks corresponding to the hydroxyl oxide standard card, while the iron phase diffraction characteristics of ordinary impregnated samples are relatively weak or have different degrees of dispersion. In the Raman spectrum, all samples retain obvious D and G bands, and I D / I G The minimal changes indicate that the loading treatment did not significantly damage the carbon skeleton structure of the activated carbon. In summary, the above results demonstrate that the process of this invention is beneficial for obtaining iron hydroxyl oxides with smaller particle size and higher dispersion, while better preserving the original carbon skeleton structure of the activated carbon.

[0070] As shown in Tables 1 and 2, the activated carbon adsorbent material prepared by this invention can maintain a good pore structure and a small iron hydroxyl oxide particle size while maintaining a high iron loading. Taking Example 1 as an example, its total iron content is 8.6 wt.%, and its BET specific surface area still reaches 862 m². 2 / g, micropore volume is 0.34 cm³ 3 The iron phase had an average particle size of 2.3 nm. Simultaneously, the adsorption capacities for As(V) and phosphate reached 58.6 mg / g and 42.8 mg / g, respectively, with a removal rate of 88.4% after 30 min. The iron leaching rate after water washing was only 0.42%, and the capacity retention rate after 5 cycles was 91.8%. Compared to the ordinary impregnated and dried sample in Control Example 1 and the commercially available activated carbon raw material in Control Example 6, the material of this application exhibited a smaller iron phase particle size, higher pore structure retention, lower iron leaching rate, and better cycling stability.

[0071] Results from different embodiments also show that precursor concentration, gel pre-absorption degree, and permeation-dissolution time all affect iron loading and pore structure retention. While excessively high precursor concentration or excessively long dissolution time can increase iron content, it will cause a decrease in specific surface area and micropore volume. Therefore, by combining precursor concentration, gel hydration state, dissolution time, and other processes, a better balance can be achieved between iron loading, pore structure retention, and adsorption performance.

[0072] As shown in Tables 3 and 4, under the same fixed-bed conditions, the breakthrough bed volume and dynamic adsorption capacity of As(V) in Example 9 were higher than those of the ordinary impregnated-dried sample in Control Example 1, and significantly higher than those of the commercially available ordinary granular activated carbon NORIT® GAC 1240 W in Control Example 6. Meanwhile, Example 9 had a lower average effluent iron concentration and a higher capacity retention rate in the 5th cycle, indicating that the in-pore iron hydroxyl oxide loading method of the present invention is beneficial to improving the utilization rate of dynamic active sites, reducing the loss of iron components during long-term water flow scouring, and improving reusability.

[0073] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an iron hydroxyl oxide-supported activated carbon adsorbent, characterized in that, Includes the following steps: S1. Using activated carbon particles as raw material, the activated carbon particles adsorb a precursor liquid to obtain wetted particles containing the precursor liquid in the carbon pores; the precursor liquid includes an iron carboxylic acid complex. S2. Remove the continuous free liquid from the outer surface of the activated carbon particles treated in step S1, so that the surface of the wet particles remains wet but there is no continuous liquid phase that can flow between the particles. S3. The activated carbon particles treated in step S2 are subjected to a gel permeation and desolvation treatment; after the permeation and desolvation treatment is completed, the activated carbon particles are separated from the gel; the gel is covalently connected with anionic groups that maintain a negative charge under the treatment conditions and do not migrate with the aqueous phase; S4. The activated carbon particles treated in step S3 are alkalized by gas-phase alkalization. S5. The activated carbon particles treated in step S4 are subjected to aging, washing and drying processes in sequence to obtain the iron hydroxyl oxide supported activated carbon adsorbent.

2. The method for preparing the iron hydroxyl oxide-supported activated carbon adsorbent according to claim 1, characterized in that, In step S1, the pH value of the precursor solution is 4.5 to 5.5, and the molar concentration of iron in the precursor solution is 0.8 to 2 mol / L.

3. The method for preparing the iron hydroxyl oxide-supported activated carbon adsorbent according to claim 1, characterized in that, In step S1, the activated carbon particles and precursor solution are placed in a vacuum container and adsorbed for 2 to 30 minutes under a pressure of -0.04 to -0.095 MPa, then the air is vented, and then the mixture is allowed to stand for 15 to 120 minutes for adsorption.

4. The method for preparing the iron hydroxyl oxide-supported activated carbon adsorbent according to claim 1, characterized in that, In step S2, one or more of the following methods are used to remove the continuous free liquid on the surface of activated carbon particles: centrifugal dehydration, air knife purging, rolling leaching, or short-time adsorption. The mass of the free liquid carried on the wetted particles after treatment is 8-15% of the dry weight of the activated carbon.

5. The method for preparing the iron hydroxyl oxide-supported activated carbon adsorbent according to claim 1, characterized in that, In step S3, the gel is an exclusion-type polymer cross-linked gel, and the anionic groups contained in the gel are carboxyl groups, carboxylate groups, sulfonate groups, or sulfate groups.

6. The method for preparing the iron hydroxyl oxide-supported activated carbon adsorbent according to claim 1, characterized in that, In step S3, the mass ratio of the moistened particles to the gel is 1:1~3; after the gel is pre-water-absorbing, it comes into contact with the activated carbon particles, and the degree of pre-water absorption of the gel is 25~60% of the equilibrium water absorption; the contact temperature between the moistened particles and the gel is 10~40 ℃, and the contact time is 30~120 min; the permeation and desolvation treatment is carried out in a closed container, and the total mass loss of the moistened particles and the gel during the permeation and desolvation process does not exceed 2%.

7. The method for preparing the iron hydroxyl oxide-supported activated carbon adsorbent according to claim 1, characterized in that, In step S4, the gas-phase alkalization method involves using ammonia steam and / or ammonia-containing humid gas generated by heating ammonium bicarbonate to alkalize the activated carbon particles. The treatment temperature is 20~70 ℃ and the treatment time is 1~12 h.

8. The method for preparing the iron hydroxyl oxide-supported activated carbon adsorbent according to claim 1, characterized in that, In step S5, the activated carbon particles treated in step S4 are aged at 40~90℃ and 70~95% relative humidity for 2~12h, washed with deionized water, and then dried at 70~120℃ for 6~12h.

9. An iron hydroxyl oxide-supported activated carbon adsorbent, characterized in that, The adsorbent is prepared by any one of the methods described in claims 1 to 8, wherein the BET specific surface area ratio of the adsorbent to the activated carbon granule raw material is 45 to 90:100; and the average particle size of the iron hydroxyl oxide in the adsorbent particles is 1 to 10 nm.

10. The application of the iron hydroxyl oxide-supported activated carbon adsorbent as described in claim 9 in water treatment, characterized in that, The adsorbent is used as a fixed-bed filter media for the removal of arsenic and / or phosphorus from water.

Citation Information

Patent Citations

  • Composite absorption material for removing arsenic from water and its preparation method

    CN100386141C

  • Arsenic removal adsorbent and preparation method thereof

    CN102114401B

  • Method for preparaing dephosphorized and ferrum-carried activated carbon adsorbent

    CN102614854A